(untitled) (Research, Society and Development, 2021)
Introduction: Dentistry has a great challenge in the fight against oral cancer, which is considered a public health problem. Thus, it is important that the population is informed about the risk factors for this disease and how to prevent it. The aim of this study is to present the oral lesions diagnosed in the oral cancer prevention campaign in the city of Fernandópolis/SP in 2017. Methodology: Initially, patients were examined by dental surgeons at basic health units and, in the presence of oral lesions, they were referred to the Center for Dental Specialties (CEO) of the municipality for re-evaluation by a specialist. Results: 720 people were examined during the oral cancer prevention campaign in the city of Fernandópolis / SP in 2017, 58 (8.05%) of whom had oral lesions and were referred for reassessment by the CEO. Only 52 attended the scheduled appointment, that is, 6 (10.3%) dropped out. Of the re-evaluated patients, 3 (5.8%) presented malignant lesions and needed to be referred for specialized treatment. The other reevaluated patients had 47 benign or potentially malignable lesions and 19 variations in normality were diagnosed. Conclusions: Given the results obtained, we could conclude that the oral cancer prevention campaign provided the diagnosis of many oral lesions even though it did not have the necessary dimension, because only a small portion of the population of the municipality was evaluated during the campaign.